A Mixed-Methods Examination of Factors Related to HPV Vaccination Promotion in Private Dental Settings, Iowa, 2019 - Askelson, Natoshia (Prev Chronic Dis, 2021)
INTRODUCTION: Human papillomavirus (HPV)-associated oropharyngeal cancer rates are rising, particularly in males, although rates of other HPV-related cancers are decreasing. Although the HPV vaccine is safe and effective, vaccination rates remain below the Healthy People 2030 goal of 80% coverage. Engaging dental providers, who have experience with patient education and oropharyngeal cancer, may prove useful in efforts to increase vaccination rates. Our research explores dental providers’ (dentists, dental hygienists) willingness to participate in continuing education about HPV, educate parents of adolescents, recommend the vaccine for adolescents, and refer parents to medical providers. METHODS: We used a mixed-methods approach and conducted a survey with dental hygienists and semistructured interviews with dental providers. We produced frequencies and descriptive statistics for all variables and used regression modeling to explore factors related to willingness to promote the HPV vaccine. We used a deductive approach to code interview transcripts. RESULTS: Regression models using survey data (n = 470) showed that after controlling for demographic and practice-level characteristics, higher levels of willingness were associated with thinking that parents would act on a recommendation and thinking that engaging in HPV promotion is within the scope of practice. Interview data reflected willingness of dental providers to work on HPV vaccination, but revealed barriers (eg, time, knowledge) that need to be addressed. DISCUSSION: Overall, dental providers expressed a willingness to participate in HPV vaccine promotion, and future efforts should focus on addressing barriers to doing so. Engaging dental providers in HPV vaccine recommendation and referral can help prevent future HPV-related cancers.